Association of ABCB1 genetic variants with renal function in Africans and in Caucasians - Elston Robert C; Bergmann Sven; Bovet Pascal; Vollenweider Peter; Johnson Toby; Maillard Marc; Eap Chin B; Bochud Murielle; Beckmann Jacques S; Waterworth Dawn M; Mooser Vincent; Gabriel Anne; et al. (BMC, 2008)
Abstract Background The P-glycoprotein, encoded by the ABCB1 gene, is expressed in human endothelial and mesangial cells, which contribute to control renal plasma flow and glomerular filtration rate. We investigated the association of ABCB1 variants with renal function in African and Caucasian subjects. Methods In Africans (290 subjects from 62 pedigrees), we genotyped the 2677G>T and 3435 C>T ABCB1 polymorphisms. Glomerular filtration rate (GFR) was measured using inulin clearance and effective renal plasma flow (ERPF) using para-aminohippurate clearance. In Caucasians (5382 unrelated subjects), we analyzed 30 SNPs located within and around ABCB1, using data from the Affymetrix 500 K chip. GFR was estimated using the simplified Modification of the Diet in Renal Disease (MDRD) and Cockcroft-Gault equations. Results In Africans, compared to the reference genotype (GG or CC), each copy of the 2677T and 3435T allele was associated, respectively, with: GFR higher by 10.6 ± 2.9 (P < 0.001) and 4.4 ± 2.3 (P = 0.06) mL/min; ERPF higher by 47.5 ± 11.6 (P < 0.001) and 28.1 ± 10.5 (P = 0.007) mL/min; and renal resistances lower by 0.016 ± 0.004 (P < 0.001) and 0.011 ± 0.004 (P = 0.004) mm Hg/mL/min. In Caucasians, we identified 3 polymorphisms in the ABCB1 gene that were strongly associated with all estimates of GFR (smallest P value = 0.0006, overall P = 0.014 after multiple testing correction). Conclusion Variants of the ABCB1 gene were associated with renal function in both Africans and Caucasians and may therefore confer susceptibility to nephropathy in humans. If confirmed in other studies, these results point toward a new candidate gene for nephropathy in humans.